THE ROLE OF PERCEIVED ORGANIZATIONAL SUPPORT IN SUPPORTING LOCAL GOVERNMENTS' TAX APPARATUS TO OPTIMIZE LOCAL TAX REVENUE - Puti Nurul Karimah; Fauzan Misra (ACCRUALS (Accounting Research Journal of Sutaatmadja), 2020)
Organizational support theory suggest that perceived organizational support may influence the employee's behavior and performance. This study aims to investigate the influence of the quality of the tax apparatus and perceived organizational support on efforts to optimize local tax revenue. To accomplish this purpose, a survey was conducted on the regional tax apparatus in Sumatera. This study uses purposive sampling involving 60 respondents. The results of this study show that the quality of the tax apparatus does not affect the efforts to optimize local tax revenue. Then, the perceived organizational support has a positive and significant influence on the effort to optimize local tax revenue. However, perceived organizational support does not moderate the influence of the quality of the tax apparatus on efforts to optimize local tax revenue. These findings imply that local governments need to improve the quality of the apparatus to obtain organizational goals. In addition, local governments need to pay attention to the employee in order to trigger organizational goals attainment.